Why is the General Ophthalmic Services (GOS) Contract that underpins primary eye care in the UK contrary to the public health interest?. Issue 7 (1st October 2014) - Shickle, D; Davey, C J; Slade, S V
Abstract : The model for delivery of primary eye care in Europe varies from country to country with differing reliance on ophthalmologists, optometrists and dispensing opticians. Comparative analysis of models has tended to focus on interprofessional working arrangements, training and regulatory issues, rather than on whether a particular model is effective for delivering public health goals for that country. National Health Service (NHS) primary eye care services in the UK are predominantly provided under a General Ophthalmic Services (GOS) Contract between the NHS and practice owners (Contractors). Over two-thirds of sight tests conducted in England, Wales and Northern Ireland and all in Scotland are performed under a GOS Contract, however many people entitled to a GOS sight test do not take up their entitlement. The fee paid for sight tests conducted under a GOS Contract in England, Wales and Northern Ireland does not cover the full cost of conducting the examination. The shortfall must be made up through profits of sale of optical appliances but this business model can be a deterrent to establishing practices within socioeconomically deprived communities, and can also be a barrier to uptake of sight tests, even though many people are entitled to a NHS optical voucher towards the cost of spectacles or contact lenses. This paper critiques the GOS Contracts within the UK. We argue that aspects of the way the GOS Contract is implemented are contrary to the public health interest and that different approaches are needed to address eye health inequalities and to reduce preventable sight loss.